Luminosity, energy and polarization studies for the Linear Collider: Comparing e(+)e(-) and e(-)e(-) for NLC and TESLA - Woods, M; Moffeit, K; Raubenheimer, T; Seryi, A; Sramek, C; Florimonte, A (2005)
We present results from luminosity, energy and polarization studies at a future Linear Collider. We compare e+e- and e -e- modes of operation and consider both NLC and TESLA beam parameter specifications at a center-of-mass energy of 500 GeV. Realistic colliding beam distributions are used, which include dynamic effects of the beam transport from the Damping Rings to the Interaction Point. Beam-beam deflections scans and their impact for beam-based feedbacks are considered. A transverse kink instability is studied, including its impact on determining the luminosity-weighted center-of-mass energy. Polarimetry in the extraction line from the IP is presented, including results on beam distributions at the Compton IP and at the Compton detector. © World Scientific Publishing Company.